The Effect of Good Corporate Governance (GCG) and Bank Size on Financial Performance with Non-Performing Financing (NPF) as a Moderating Variable in Islamic Banking in 2019-2023 - Muhammad Asril Maulana; Agil Krisna Rivanda; Galih Nugraha (Al-Makki Publisher, 2025)
The growth of the Islamic banking industry in Indonesia shows a significant increase, which triggers competition between Islamic banks and conventional banks. In this context, Good Corporate Governance (GCG) and bank size play an important role in influencing financial performance, as measured by Return on Assets (ROA). This study aims to analyze the effect of GCG and bank size on financial performance with Non-Performing Financing (NPF) as a moderating variable. This study uses data from 10 Islamic banks registered with OJK during the 2019-2023 period, using purposive sampling method. The data were analyzed using panel regression and Moderated Regression Analysis (MRA) to test the proposed hypothesis. The results showed that GCG and bank size have a positive and significant effect on ROA. However, NPF is not able to moderate the effect of GCG and bank size on ROA. This finding confirms the importance of good GCG implementation and effective risk management in improving the financial performance of Islamic banks. Although NPF does not moderate the relationship between GCG and bank size on ROA, risk management is key in maintaining good financial performance. An increase in the number of independent commissioners is expected to support better company conditions. This study concluded that GCG and bank size have a significant influence on the financial performance of Islamic banks. To improve financial performance, it is important for Islamic banks to optimize the implementation of GCG and manage financing risks well. Future research is recommended to expand the number of samples and variables studied in order to obtain more accurate and comprehensive results.